Freezing Of Single Woman's Egg Cells According To Sadd Al-Dzari'ah Analysis - Arif, Achmad; Awalia, Fadhila Tianti Mudi; Lutfiah, Asti (Fakultas Syariah INSURI Ponorogo, 2024)
Egg freezing is a form of artificial insemination method legally permitted in emergencies. Still, the current phenomenon is that many women use it to postpone marriage and postpone having children at a young age with the desire to have children in their old age. Therefore, the author is interested in studying and discussing egg freezing with sadd dzari'ah analysis. This discussion aims to discover how egg freezing is carried out in women and how to analyze sadd dzaro'i in women who use the egg-freezing method. This research uses normative research that examines document studies using secondary data from legislation and legal theory. This normative research uses qualitative analysis from books, journals, and relevant articles to collect data using literature study techniques to find research results based on the Al-Qur'an and Hadith. As a result of this research, the author examines that egg freezing is permitted with syar'i conditions. However, what happens when it is used is non-shar'i washilah, so the impact on the mafsadah is greater than the benefit. Thus, the author concludes that it is better to abandon egg freezing to prevent greater harm, such as mixing egg cells. So, preventing something is better than bringing about forgiveness.